Jobbcoachen i betraktarens öga : Klienters upplevelser av jobbcoachers bemötande hos Arbetslivsresurs i Luleå - Rönnqvist, Ninni (2012)
Coaching is built on trust and a confiding relationship between coach and coachee. A coach is naturally interested in the coachee´s perception of his or her performance, to use and develop positively perceived behavior, or to correct less positively perceived behavior. The purpose of this thesis was to follow up how coachees at Arbetslivsresurs in Luleå perceived their job coach´s performance. Seven coachees were interviewed about their coach´s behavior, their own expectations and perceived effects due to the coaching process. The results show that in six cases of seven the coach´s performance were perceived very positively. The coach´s behavior and the effects of coaching had an impact on how the performance was perceived, but above all stands the coachee´s motivation as significant for how the coaching process was experienced. The results also show that goal-setting and action planning were not practiced in all cases. Based on the results it is suggested that the coach in the initial phase of the coaching process focuses on the coachee´s motivation through systematic inclusion of Motivational Interviewing, MI. Also the coaching tools goal-setting, action planning and follow-up should be standard practice in order to help coachees maintain motivation for change. Validerat; 20120621 (anonymous)